Design and Implementation of a Backtracking Wormhole Switch using MARX units for Mesh Topology (International Journal of Engineering and Computer Science, 2014)
Network-on-Chip (NoC) is supposed to be adopted by the designers as a substitute for buses and dedicated wire interconnection schemes in future complex SoCs. Compact and power efficient design of basic routing element (router or switch) is an important part of the NoC design. Several switch implementations for different topologies of NoCs are proposed. This project presents the design of Backtracking Wormhole Switch. The switching mechanism used is circuit-switching approach. The proposed circuit-switched router, based on a Backtracking probing path setup, operates with new MARX units, and allows for efficient low latency Wormhole switch implementation. The switch can support a dead- and live-lock free dynamic path-setup scheme. The backtracked routing Network-on-Chip provides guaranteed and energy-efficient data transfer. The backtracking wormhole switch architecture is considered for use under a mesh/torus topology because of its good path diversity.